VideoHound's world cinema : the adventurer's guide to movie watching - Wilhelm, Elliot (Detroit : Visible Ink Press, 1999)
Wilhelm examines more than 800 movies from the audience's point of view, with an eye toward connections to other films and filmmakers, linking the international cinema with the American filmmaking experience. 100 photos
Includes indexes.
Keywords: Foreign films -- Catalogs; Video recordings -- Catalogs; Grabaciones en cintas de video